THE EFFECT OF BUSINESS IMAGE, USER IMAGE, AND PRODUCT IMAGE ON CONSUMER LOYALTY - Muhammad Khairul; Nuri Aslami (International Journal Labs, 2022)
As a primary factor in satisfaction and loyalty, service quality and image has been given a lot of attention This research used a sample of 50 respondents and analyzed the data using structural equation modeling Findings reveal that service quality and corporate image are antecedents of customer satisfaction, but customer satisfaction surprisingly does not have positive and significant effect on customer loyalty. The implications for service providers in any platform service industry is that customer satisfaction hasnot key success to loyalty but continuously improvesthe quality of service and corporate image of satisfaction, but it creates loyalty to buy services and recommend to others